Dual origin of melanocytes defined by Sox1 expression and their region‐specific distribution in mammalian skin. (24th January 2013) - Yoshimura, Naoko; Motohashi, Tsutomu; Aoki, Hitomi; Tezuka, Ken‐ichi; Watanabe, Natsuki; Wakaoka, Takanori; Era, Takumi; Kunisada, Takahiro
<x xml:space="preserve">Abstract</x> Melanocytes are pigment‐producing cells generated from neural crest cells (NCCs) that delaminate from the dorsal neural tube. The widely accepted premise that NCCs migrating along the dorsolateral pathway are the main source of melanocytes in the skin was recently challenged by the finding that Schwann cell precursors are the major cellular source of melanocytes in the skin. Still, in a wide variety of vertebrate embryos, melanocytes are exclusively derived from NCCs. In this study, we show that a NCC population that is not derived from Sox1+ dorsal neuroepithelial cells but are derived from Sox1− cells differentiate into a significant population of melanocytes in the skin of mice. Later, these Sox1− cells clearly segregate from cells that originated from Sox1+ dorsal neuroepithelial cell‐derived NCCs. The possible derivation of Sox1− cells from epidermal cells also strengthens their non‐neuroepithelial origin.